Plant-wide control design based on steady-state combined indexes - Zumoffen, David Alejandro Ramon (2016)
This work proposes an alternative methodology for designing multi-loop control structures based on steady-state indexes and multi-objective combinatorial optimization problems. Indeed, the simultaneous selection of the controlled variables, manipulated variables, input-output pairing, and controller size and interaction degree is performed by using a combined index which relies on the sum of square deviations and the net load evaluation assessments in conjunction. This unified approach minimizes both the dynamic simulation burden and the heuristic knowledge requirements for deciding about the final optimal control structure. Further, this methodology allows incorporating structural modifications of the optimization problem context (degrees of freedom). The case study selected is the well-known Tennessee Eastman process and a set of simulations are given to compare this approach with early works.